A consensus model for Delphi processes with linguistic terms and its application to chronic pain in neonates definition - Agell, Núria; van Ganzewinkel, Christ Jan; Sánchez, Mónica; Roselló, Llorenc; Prats, Francesc; Andriessen, Peter (Applied soft computing, 2015)
[Display omitted] This paper proposes a new model of consensus based on linguistic terms to be implemented in Delphi processes. The model of consensus involves qualitative reasoning techniques and is based on the concept of entropy. The proposed model has the ability to reach consensus automatically without the need for either a moderator or a final interaction among panelists. In addition, it permits panelists to answer with different levels of precision depending on their knowledge on each question. The model defined has been used to establish the relevant features for the definition of a type of chronic disease. A real-case application conducted in the Department of Neonatology of Máxima Medical Center in The Netherlands is presented. This application considers the opinions of stakeholders of neonate health-care in order to reach a final consensual definition of chronic pain in neonates.